Liquids, solutions, and interfaces : from classical macroscopic descriptions to modern microscopic details - Fawcett, W. Ronald (OUP E-Books., 2004)
Fawcett (chemistry, University of California-Davis) introduces modern topics in solution chemistry to senior undergraduates and graduate students who have completed two semesters or three quarters of chemical thermodynamics and statistical mechanics.